Food Suplements During Pregnancy Benefits and Risks: A Literature Review - Stoilova, Lili; Stoilov, Boris; Staynova, Radiana (European Scientific Journal, ESJ, 2019)
Pregnancy is a physiological condition accompanied by a multitude of morphological, physiological and metabolic changes induced by the dynamic hormonal activity of the woman’s body. These changes are associated with an increased need for nutrient intake. The lack of proper nutrition or irrational use of dietary supplements may have deleterious effects on both the mother and the developing fetus. The optimized intake of microelements and vitamins could be beneficial and even prevent common pathological conditions which frequently occur during pregnancy. The aim of the current review is to evaluate the potential benefits and risks associated with the intake of food supplements during pregnancy. Relevant publications were searched and analyzed using the following data bases: MEDLINE/PubMed, Scopus, Web of Knowledge, and Internet. Numerous authors support the opinion that the lack of obligatory quality control of food supplements is associated with many low-quality products which could have harmful health effects.